2015
DOI: 10.1177/0020872815594225
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory comparative study of perspectives on non-suicidal self-injurious behaviors among social work students in the United States, Greece, Cyprus, and Jordan: Implications for social work practice and education

Abstract: There has been a call for cross-cultural research in the understanding of non-suicidal self-injury (NSSI). The purpose of this study was to explore the influence of ethnicity and culture on the understanding of NSSI among social work students in the United States, Greece/Cyprus, and Jordan. A convenience sample of 438 social work students was used. Participants completed a 60-item questionnaire. Results revealed statistically significant differences in students' knowledge and cultural beliefs about NSSI by cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 62 publications
(95 reference statements)
0
19
0
Order By: Relevance
“…Kokaliari et al (2017) found statistically significant differences in overall knowledge of NSSI between students from the USA, Jordan, and Greece/Cyprus. It was found that US students' knowledge of NSSI was more accurate than Greeks/Cypriots and Jordanian students, with authors identifying this may be related to the amount of time social work curriculum has been delivered (the USA has a 100‐year history in social work education, compared to 11 to 50 years in Greece/Cyprus and Jordan (Kokaliari et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Kokaliari et al (2017) found statistically significant differences in overall knowledge of NSSI between students from the USA, Jordan, and Greece/Cyprus. It was found that US students' knowledge of NSSI was more accurate than Greeks/Cypriots and Jordanian students, with authors identifying this may be related to the amount of time social work curriculum has been delivered (the USA has a 100‐year history in social work education, compared to 11 to 50 years in Greece/Cyprus and Jordan (Kokaliari et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Studies included participants from several disciplines including nursing (Hales, 1996; Liu et al, 2018; Patterson et al, 2021; Schafer et al, 2011), social work (Kokaliari et al, 2017), and health sciences (Al‐Krenawi et al, 2009). Due to the heterogeneity of the studies, the review is unable to determine whether one discipline has a better understanding of mental health than another.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations